Summary: creating systems innovation platforms for transformative pathways in circular economy - Sobratee‑Fajurally, Nafiisa; Nhamo, L.; Mabhaudhi, Tafadzwanashe (CRC Press, 2024)
The chapters in this book cover multi-dimensional aspects of resource use efficiency framed around the circular economy (CE) and how its intertwined domains enable transformative approaches. Various epistemic standpoints are discussed, ranging from systems optimisation versus systems application challenges in sludge waste management in Sweden, gendered and intersectionality considerations, the efficacy of user interface in WASH initiatives from a socio-technical perspective, integrated strategies for climate change adaptation and pandemic preparedness, and CE implications at multiple governance levels with examples from Sub-Saharan Africa. This leads to the insight that whereas the various resource strategies grouped under the CE’s banner are not new individually, the concept offers a new framing of these strategies by drawing attention to their capacity to prolong resource use and sustain ecosystems as well as to the interrelationships between these strategies. This chapter aims at synthesising the learning outcomes from each chapter. More specifically, it seeks to demonstrate how tension arising between the dichotomy of short-term efficiency versus large-scale transition or mandated sector-specific achievements versus long-term systemic resilience outcomes can be accommodated if we can shift our perspective from seeing these as dichotomies to one where the evolutionary principle of complex systems is envisioned (Siegenfeld & Bar-Yam, 2020). Since transformative approaches to CE are complex, tensions due to competing strategies are inevitable. One of the ways to view the transformative potential of CE is to understand the nature and scale of change that any intervention seeks to address. Considering the topics covered in this work, six leverage points framed around transformative CE are discussed. These are organised as (i) realising that the current equilibrium is outdated and skewed towards linearity such that impacts are additive but non-systemic, (ii) creating a new culture for enabling transformative patterns by connecting actors who share a new set of values, (iii) enabling Community of Practice (CoP) that share a common identity, (iv) connecting resources in novel ways by repurposing existing capacities, that is, extending the ontology of the CE, (v) institutionalising and supporting new networked configurations till normalisation, and (vi) impacts become systemic through synergies, trade-offs and comprise are negotiated and new patterns co-exist and are visible. The theme from each chapter is plotted against these leverage points, as shown in Figure 15.1.